Methodological Proposal to Define the Degree of Automation in the Sanitary Industry in Chile to Adapt to Climate Change - Oddershede-Herrera, A; Palominos-Belmar, P; Quezada-Llanca, L; Macuada-Silva, C (Springer, 2021)
This study proposes a methodology to support the decision making to improve the efficiency of the technological standard in the sanitary industry facilities considering the climate change effects. Nowadays, the population necessities in terms of environment, quality and continuity of service are constantly increasing. In this regard, the sanitary industry is adopting new technologies for its processes, with the purpose that be a factor for service improvement. At present time, the Chilean sanitary industry is concern about the degree of automation and the infrastructure requirements, since they are the main critical factors for future investment planning. Therefore, it is necessary to determine the current level of the telecontrol system facilities and generate actions to make improvements in those processes that show a poor quality of service. The research methodology is based on case study, integrating planning processes, data analysis, scoring method interacting with multicriteria approach. This paper emphasis on developing a decision model by the use of the Analytical Hierarchy Process (AHP), to identify the priority facilities that should improve their technological standard. A case study incorporating climate change factors is pursued in a metropolitan sanitary company in Chile, accomplishing the automation degree of a telecontrol system for the real case. These results give place to elaborate an investment plan that can be converted into action plans for a sanitary company. © Springer Nature Switzerland AG 2021.